Genome-Wide Identification, Expression Profiling, and Functional Validation of Oleosin Gene Family in Carthamus tinctorius L. - Lu, Yubin; Chi, Menghan; Li, Lixia; Li, Haoyang; Noman, Muhammad; Yang, Ying; Ji, Kun; Lan, Xinxin; Qiang, Weidong; Du, Linna; Li, Haiyan; Yang, Jing (Frontiers in Plant Science, 2018)
Carthamus tinctorius L. commonly known as safflower is an important oilseed crop containing oil bodies. Oil bodies are intracellular organelles in plant cells for storing triacylglycerols (TAGs) and sterol esters. Oleosins are the most important surface proteins of the oil bodies. We predicted and retrieved the sequences of eight putative Ct-oleosin (Carthamus tinctorius-oleosin) genes from the genome database of safflower. The bioinformatics analyses revealed the size of their open reading frames ranging from 414 to 675 bp, encoding 137 to 224 aa polypeptides with predicted molecular weights of 14.812 to 22.155 kDa, all containing the typical ‘‘proline knot’’ motif. RT-qPCR determinated the spatiotemporal expression pattern of Ct-oleosin genes which gradually increasesd and peaked during flowering and seed ripening and decreased thereafter. To validate their role in plant development, we transformed and overexpressed these eight putative Ct-oleosin genes in Arabidopsis. Overexpressing Ct-oleosins did not affect leaf size but siliques length was altered. Arabidopsis transformed with Ct-oleosin3, 4 and 5 grew longer siliques than wild type without altering seed quantity. The 100-grain weight of the transgenic Arabidopsis seeds was slightly more than that of the wild-type. The seeds germination rate of overexpressing Ct-oleosin4 and 6 were slightly lower as compare to the wild-type Arabidopsis and others had been risen. The overexpression of Ct-oleosin genes consequently consequently elevated oil content in the seeds of transgenic Arabidopsis. Our findings not only provide an approach to increase oil content but they are also important in fully deciphering the intricate mechanisms of oil body synthesis.